Identification of intestinal mediators of Caenorhabditis elegans DBL-1/BMP immune signaling shaping gut microbiome composition - Dan Kim; Kenneth Trang; Barbara Pees; Siavash Karimzadegan; Rahul Bodkhe; Sabrina Hammond; Michael Shapira (mBio)
ABSTRACT The composition of the gut microbiome is determined by a complex interplay of diet, host genetics, microbe-microbe interactions, abiotic factors, and stochasticity. Previous studies have demonstrated the importance of host genetics in community assembly of the Caenorhabditis elegans gut microbiome and identified a central role for DBL-1/BMP immune signaling in determining the abundance of gut Enterobacteriaceae. However, the effects of DBL-1 signaling on gut bacteria were found to depend on its activation in extra-intestinal tissues, highlighting a gap in our understanding of the proximal factors that determine microbiome composition. In the present study, we used RNA-seq gene expression analysis of wildtype, dbl-1 and sma-3 mutants, and dbl-1 over-expressors to identify candidate DBL-1/BMP targets that may mediate the pathway’s effects on gut commensals. Bacterial colonization experiments in mutants, or following RNAi-mediated knock-down of candidate genes specifically in the intestine, demonstrated their local contribution to intestinal control of Enterobacteriaceae abundance. Furthermore, epistasis analysis suggested that these contributions were downstream of the DBL-1 pathway, together suggesting that examined candidates were intestinal effectors and mediators of DBL-1 signaling, contributing to the shaping of gut microbiome composition.IMPORTANCECompared to the roles of diet, environmental availability, or lifestyle in determining gut microbiome composition, that of genetic factors is the least understood and often underestimated. The identification of intestinal effectors of distinct molecular functions that control enteric bacteria offers a glimpse into the genetic logic of microbiome control as well as a list of targets for future exploration of this logic.